PENERAPAN DIGITAL SIGNATURE PADA TRANSKRIP NILAI SEBAGAI OTENTIKASI DATA - G.A, Ibnu Berliyanto; Hamzah, Amir; Raharjo, Suwanto (Jurnal Script, 2014)
ABSTRACTAlong with the rapid development of information technology especially which is related to computers and internet, data security is a complex issue, one of the problem is data manipulation. One way to prevent this is to create a data security system that can prevent data manipulation activities and ensure that the data is authentic. In this case, data security technology using a digital signature is a quite right effort . The application of digital signature methods on transcripts with a web-based application is one of the solutions in the application of data security systems. The application is built using a digital signature with function of CRC32 hash algorithm that will generate a CRC value based on certain bits within the file, and then combined with a unique value for the variable then integrated with database and included on the transcript as evidence of authentic data.The results of this application is a security data system which show the transcripts using digital signature, as data authentication attempts. With the digital signature application hopefully can help to reduce any data manipulation activities, especially academic data which is one of the manipulated data is sensitive and too risky to be manipulated.Keywords : Transcript, digital signatures, hash function, CRC32, authentic.